Development of auto parts and engine assembly process for new models of vehicle (Revista Cientifica Ingenio Magno, 2020)
The article comes up from the development of a project portrayed in a significant improvement project from the technical point of view of vehicles sold in Colombia, to which an engine optimization was applied. The document introduces the economic vision of the automotive sector, as well as a brief overview of the problems that originated the development of the project. The state of the art related to product development processes in the automotive industry is presented and a description of recent design changes associated with engines are included. Finally, a description is made of the most relevant aspects of the development of the project that involves engineering work in an assembled vehicle company and five local auto parts manufacturing companies.
Keywords: Design; Vehicle Systems; Manufacturing Processes; Climate Perimeter; Exhaust Lines; Fuel Line Vehicle Assembly